Divorce and remarriage after abuse: Conservative Protestant responses - Leong, Rebecca (Theology, 2018)
Conservative Protestant scholars' views on divorce and remarriage after abuse vary significantly, each with its strengths and possible deficiencies. A more holistic virtues-based approach may assist.